2019
DOI: 10.1007/s42452-019-0321-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fe3O4 nanoparticle on nutrient accumulation in common bean plants grown in soil

Abstract: The effect of Fe 3 O 4 nanoparticles (NPs) on chemical properties of the soil rhizosphere and on the accumulation of nutrients in common bean plants was studied for two different concentrations of Fe 3 O 4 NPs. The root-to-leaves translocation index for micro-and macronutrients was calculated. The results showed that Fe 3 O 4 NP treatments had a significant effect (P < 0.05) on the chemical properties of soil rhizosphere in terms of an increase in the contents of total P, extractable P, total K, extractable K,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…For instance, Souza et al (2019) reported a greater capability in the roots, stems, and leaves of Fe 3 O 4 −NP-treated common bean plants to take up the nutrients from the soil suggested a beneficial effect of Fe 3 O 4 ̲ −NP for plant development and health. 40 41 In our study, the growth and nutritional values of mungbean seedlings increased with the nZnS application. Therefore, we hypothesize that treated plants with enhanced growth and nutrition will produce fruits with improved nutritional values.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…For instance, Souza et al (2019) reported a greater capability in the roots, stems, and leaves of Fe 3 O 4 −NP-treated common bean plants to take up the nutrients from the soil suggested a beneficial effect of Fe 3 O 4 ̲ −NP for plant development and health. 40 41 In our study, the growth and nutritional values of mungbean seedlings increased with the nZnS application. Therefore, we hypothesize that treated plants with enhanced growth and nutrition will produce fruits with improved nutritional values.…”
Section: Resultssupporting
confidence: 50%
“…Also, our study was designed according to some previous studies, where NP treatments enhanced plant growth and nutrition and produced fruits with improved nutritional values. For instance, Souza et al (2019) reported a greater capability in the roots, stems, and leaves of Fe 3 O 4 –NP-treated common bean plants to take up the nutrients from the soil suggested a beneficial effect of Fe 3 O 4 ̲−NP for plant development and health . Mahmoud et al (2019) reported maximum vegetative growth, leaf pigments, and root quality in red radish plants treated with ZnO + FeO NPs .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In particular, the low synthesis of phenols contributed to an increase in the level of nitrogen in plants and a decrease in the supply of phosphorus and potassium. The application of Fe 3 O 4 nanoparticles positively affected the accumulation of phosphorus, potassium, calcium, manganese, and iron in the roots, stems, and leaves of plants (Souza et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Studies related to the effects of magnetite (Fe 3 O 4 ) nanoparticles on germination, plant growth, and antioxidative enzymes of wheat and other plants, are included in the literature (De Souza et al 2021;Iannone et al, 2016). De Souza et al (2019) showed that the Fe 3 O 4 nanoparticles significantly increased the soil nutrient content and Iannone et al (2016) also indicated that the Fe 3 O 4 nanoparticles ( ̴ 11 nm) can be used in agricultural applications because of its non-toxic feature for wheat plants. Although hydroxyapatite, obtained from eggshell, is generally used in many fields, such as biomedicals as bone substitute, regenerative dentistry, ceramic production, and water and air treatment as absorbent (Girelli, Astolfi, and Scuto, 2020), studies about the application of hydroxyapatite (HAp) on agriculture is very limited (Rop et al, 2018).…”
Section: Introductionmentioning
confidence: 99%